Implementation of Management Functions in The Management of Medical and Non-Medical Waste in Hospitals: A Study on Harapan Sehat Bumiayu Hospital - Abdul Fikri; Kamal Ludin; Ahmad Fariq Asybal Aufa; Sitti Faoziyah (Journal of Social Science, 2026)
Hospitals are healthcare institutions that produce significant amounts of medical and non-medical waste daily. Waste management that does not meet standards has the potential to negatively impact human health, the safety of healthcare workers, and environmental degradation. This study aims to analyze the implementation of management functions including planning, organizing, implementing, and supervising (POAC) in medical and non-medical waste management at Harapan Sehat Bumiayu Hospital, and to identify obstacles that hinder its implementation. The study used a qualitative approach with a descriptive case study design. Data were collected through field observations, semi-structured interviews with seven key informants, and documentation, then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results show that the four management functions have been implemented through provision of facilities and scheduling of waste collection (planning), clear division of tasks among staff (organizing), routine implementation of waste collection and transportation accompanied by the use of PPE (implementation), and daily monitoring and periodic institutional audits (supervision). However, several obstacles remain, including indiscipline among some staff in waste sorting and limited supporting facilities in some service units. Effective waste management contributes positively to hospital environmental cleanliness, infection prevention, and improved occupational safety for healthcare workers.